A cost‐efficient QoS‐aware analytical model of future software content delivery networks. Issue 4 (31st August 2020) - Otero, Beatriz; Rodríguez, Eva; Rojas, Otilio; Verdú, Javier; Costa, Juan José; Alejandro Pajuelo, Manuel; Canal, Ramón
Summary: Freelance, part‐time, work‐at‐home, and other flexible jobs are changing the concept of workplace and bringing information and content exchange problems to companies. Geographically, spread corporations may use remote distribution of software and data to attend employees' demands, by exploiting emerging delivery technologies. In this context, cost‐efficient software distribution is crucial to allow business evolution and make IT infrastructures more agile. On the other hand, container‐based virtualization technology is shaping the new trends of software deployment and infrastructure design. We envision current and future enterprise IT management trends evolving towards container‐based software delivery over hybrid content delivery networks (CDNs). This paper presents a novel cost‐efficient QoS‐aware analytical model and a hybrid CDN–peer‐to‐peer (P2P) architecture for enterprise software distribution. The model would allow delivery cost minimization for a wide range of companies, from big multinationals to SMEs, using CDN–P2P distribution under various industrial hypothetical scenarios. Model constraints guarantee acceptable deployment times and keep interchanged content amounts below the bandwidth and storage network limits in our scenarios. Indeed, key model parameters account for network bandwidth, storage limits, and rental prices, which are empirically determined from their offered values by the commercial delivery networks KeyCDN, MaxCDN, CDN77, and BunnyCDN. This preliminary study indicates that MaxCDN offers the best cost‐QoS trade‐off. The model is implemented in the network simulation tool PeerSim and then applied to diverse testing scenarios by varying company types, number and profile (either, technical or administrative) of employees, and the number and size of content requests. Hybrid simulation results show overall economic savings between 5% and 20%, compared to just hiring resources from a commercial CDN, while guaranteeing satisfactory QoS levels in terms of deployment times and number of served requests. Abstract : The key contributions of this paper are (1) definition of essential features characterizing software distribution for container‐based delivery; (2) definition of a hybrid CDN–P2P architecture for low‐priced high QoS software applications; (3) definition of a novel cost‐efficient QoS‐aware analytical model that minimizes deployment costs and satisfies users' QoS in terms of response time and number of served requests; (4) identification and study of realistic scenarios for model application; and (5) model analysis and assessment in all scenarios under consideration.